PERMAINAN LEMPAR TANGKAP BOLA UNTUK MENINGKATKAN MOTORIK KASAR ANAK AUTIS DI SLB PURNAMA ASIH - Naurah Rohadatul 'Aisy; Budi Susetyo; Dudi Gunawan (Study program PGSD FKIP Universitas Bung Hatta, 2024)
Autistic children with impaired motor neurodevelopment are characterized by motor inhibitions. Motor skills of autistic children can be improved through appropriate physical education, especially through sports or games. The aims of this research was to determine whether the game of throwing catch the ball can improve the gross motor skills of autistic children. The method used in this research is Single Subject Research (SSR) with research procedures using the A-B-A design. The result of this research indicate that ball throwing games can improve the gross motor skills of autistic children.